2020
DOI: 10.1002/ijc.32882
|View full text |Cite
|
Sign up to set email alerts
|

Integrated clinicomolecular characterization identifies RAS activation and CDKN2A deletion as independent adverse prognostic factors in cancer of unknown primary

Abstract: Cancer of unknown primary (CUP) denotes a malignancy with histologically confirmed metastatic spread while the primary tumor remains elusive. Here, we address prognostic and therapeutic implications of mutations and copy number variations (CNVs) detected in tumor tissue in the context of a comprehensive clinical risk assessment. Targeted panel sequencing was performed in 252 CUP patients. 71.8% of patients had unfavorable CUP according to ESMO guidelines. 74.7% were adeno‐ and 13.7% squamous cell carcinomas. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…However, the lack of universal availability of molecular profiling for CUP and validation of these biomarkers, limits current inclusion in a clinic ready nomogram. (37,40) Additionally, due to low prevalence of these biomarkers and limited access to testing and therapy in CUP, we believe that the nomogram will play a critical role in management of a substantial subset of patients with CUP. Ongoing efforts will be needed to study continued performance and refinement as understanding of molecular biology improves and as more therapies become available for CUP patients.…”
Section: Internal and External Validation And Performance Of Nomogrammentioning
confidence: 99%
“…However, the lack of universal availability of molecular profiling for CUP and validation of these biomarkers, limits current inclusion in a clinic ready nomogram. (37,40) Additionally, due to low prevalence of these biomarkers and limited access to testing and therapy in CUP, we believe that the nomogram will play a critical role in management of a substantial subset of patients with CUP. Ongoing efforts will be needed to study continued performance and refinement as understanding of molecular biology improves and as more therapies become available for CUP patients.…”
Section: Internal and External Validation And Performance Of Nomogrammentioning
confidence: 99%
“…[ 10 ] The latest research also found that inferior prognosis was associated with KRAS activation by point mutation and gene amplification, and TP53 mutations were associated with an adverse prognosis in the SCC subgroup and in females. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…NGS panel sequencing is routinely performed at our center to identify molecular targets 10 . Library preparation for the capture‐based TruSight Oncology 500 panel (Illumina) was performed as previously described 25 .…”
Section: Methodsmentioning
confidence: 99%
“…Several next‐generation panel sequencing‐based studies have elucidated the mutational landscape in CUP. These studies have consistently demonstrated that the mutational spectrum in CUP is diverse, with TP53 , KRAS , CDKN2A/B , MYC , PIK3CA , ARID1A , ERBB2 , and NOTCH1 genes most frequently harboring alterations 4–10 . With respect to prognosis CDKN2A/B deletion and KRAS activation have been identified as adverse prognostic markers 10 …”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation